2011
DOI: 10.2174/138161211796904768
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy and Disease: New Avenues for Pharmacological Intervention

Abstract: The process of intracellular macromolecular degradation known as macroautophagy has long been associated with the degradation of mitochondria. Recent studies have provided evidence that the process of mitochondria degradation via autophagy, now referred to as mitophagy, appears to be specifically targeted to mitochondria and highly regulated under both physiologic and pathologic conditions. This article provides a review of key developments in mitophagy research, including background information on the history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…115,116 In this sense, induction of autophagy has given promising results in mouse models of Alzheimer's disease 117 and other neurodegenerative diseases. 118 Further, the increased genomic instability observed in parkin-deleted cells could also be explained by the observation that parkin translocates from the cytosol to the nucleus where it participates in DDR after DNA damage. 115,116 Therefore, the parkin protein is an important factor in both DDR and autophagic removal of injured mitochondria.…”
Section: Parpmentioning
confidence: 99%
“…115,116 In this sense, induction of autophagy has given promising results in mouse models of Alzheimer's disease 117 and other neurodegenerative diseases. 118 Further, the increased genomic instability observed in parkin-deleted cells could also be explained by the observation that parkin translocates from the cytosol to the nucleus where it participates in DDR after DNA damage. 115,116 Therefore, the parkin protein is an important factor in both DDR and autophagic removal of injured mitochondria.…”
Section: Parpmentioning
confidence: 99%
“…Similar to the proposed dual roles of autophagy in cancers, mitophagy could be a double-edged sword in the development of cancer [16,109]. During the early stage of cancer development, mitophagy functions to effectively remove damaged mitochondria to maintain the well-being of the cells and to prevent the occurrence of cancers [16].…”
Section: Src Kinase/fundc1 Axis In Cancermentioning
confidence: 87%
“…However, phosphorylation of these sites is not required for Atg32-Atg8 interaction [65]. Likewise, phosphorylation of Ser-17 and Ser-24 of Bnip3 also promotes its binding to LC3-B and GATE- 16 What are the kinases and phosphatases that mediate this reversible phosphorylation? A recent report using kinase screening showed that casein kinase 2 (CK2) phosphorylates the OMM protein Atg32 at Ser-114 and Ser-119 in vitro to promote its interaction with the cytosolic adaptor protein Atg11 in yeast, thus resulting in recruitment into vacuoles and mitophagy [67 •• ] Furthermore, CK2 inhibition selectively prevents Atg32-Atg11 interaction-dependent mitophagy without affecting the Cvt pathway, pexophagy and macroautophagy [67 •• ].…”
Section: Kinases and Phosphatases In Mitophagymentioning
confidence: 99%
See 2 more Smart Citations